Selective changes in cholesterol metabolite levels in plasma of breast cancer patients after tumor removal - Soucek, Pavel; Vrana, David; Ueng, Yune-Fang; Wei, Shouzou; Kozevnikovova, Renata; Guengerich, Frederick Peter (Clinical chemistry and laboratory medicine, 2018)
INTRODUCTION: Oxygenated metabolites of cholesterol (“oxysterols”) can influence carcinogenesis and contribute to resistance to endocrine therapy, an effect mostly described in vitro. OBJECTIVES: We sought to establish a method for screening plasma levels of oxysterols in breast cancer patients, estimate their individual variability and detection limits, and provide basic information about their roles in tumor biology. METHOD: Liquid-chromatography coupled with tandem mass spectrometry was used for determination of levels of 25-hydroxycholesterol, 27-hydroxycholesterol, 7α-hydroxycholesterol, and 7-ketocholesterol in plasma sample pairs from patients before and 12–24 months after surgical removal of tumors (n=24). Deuterated standards of all oxysterols were used for method validation. RESULT: All oxysterols were successfully detected in patient plasma samples. A significant increase in the level of 7-ketocholesterol was observed in the samples following tumor removal and the start of therapy compared to the sampling before (p=0.002). This increase was unrelated to personal characteristics of patients, expression of estrogen receptor, or to adjuvant therapy type. CONCLUSION: This study shows, for the first time, that circulating levels of oxysterols, especially 7-ketocholesterol, may reflect the presence of tumor cells in patients.
Keywords: Humans; estrogen; oxysterols; plasma; breast cancer; Cholesterol; Female; therapy; nádory prsu; Breast Neoplasms; cholesterol; lidé; ženské pohlaví